Motivational and emotional factors of academic achievement in mathematics in early adolescence - Poredoš, Mojca (Pedagoška obzorja, 2017)
The aim of our study was to examine the relationship between motivational and emotio - nal factors and learning performance in the period of early adolescence. The sample consisted of 5th , 6th and 7th grade students (N = 599 girls), who completed questionnaires on motivational goal orientations, attitudes towards mathematics and anxiety in mathematics. Final grades and National Examination Test (NET) scores in mathematics were used as indicators of students' academic success. The results showed significant yet small effects of grade and gender. The 5th graders reported higher motivation and more positive attitudes towards mathematics than 6th and 7th graders. Furthermore, 5th graders experienced higher anxiety regarding social evaluation in mathematics than 6th graders. Girls reported higher mastery orientation, more positive attitudes towards mathematics, higher levels of school anxiety, and higher final grade in mathematics than boys. Final grade in mathematics from the previous years, gender, grade, cognitive anxiety, and liking mathematics were all significant predictors of the final grade in mathematics.
Keywords: osnovne šole; primary school; mladostniki; early adolescence; anksioznost; school anxiety; learning; učenje; motivacija; motivation; attitudes; čustva; učna uspešnost; academic achievement; matematika; mathematics; emotions; učenci; zgodnje mladostništvo; students; raziskave; anxiety; research